SYNCHRONIZATION TECHNIQUE FOR ORTHOGONAL TIME FREQUENCY SPACE (OTFS) SYSTEM - Wahmilyana Asril, Bella
Synchronization in Orthogonal Time Frequency Space (OTFS) communication systems faces specific challenges, particularly in high-mobility wireless environments. In recent years, OTFS has gained significant attention from researchers in the field of wireless communication, as it is expected to be a more robust modulation technique for overcoming challenges in wireless environments. Carrier Frequency Offset (CFO) is one of the primary issues that can disrupt OTFS kinerjance. The main objective of this research is to develop an effective synchronization mechanism for precise CFO estimation to ensure robust signal reception at the receiver. The proposed synchronization technique employs the preamble method, utilizing two types of preambles: the Zadoff-Chu (ZC) sequence and the IEEE 802.11a standard. Testing was conducted by transmitting data in the form of images and text. The kinerjance of the synchronization technique was evaluated using Mean Square Error (MSE). The test results indicate that the ZC sequence preamble method provides better outcomes compared to other methods, and longer preamble lengths also positively impact the performance of CFO synchronization techniques.